A Novel PCR-Based Approach for Accurate Identification of Vibrio parahaemolyticus - Li, Ruichao; Chiou, Jiachi; Chan, Edward Wai-Chi; Chen, Sheng (Frontiers in Microbiology, 2016)
A PCR-based assay was developed for more accurate identification of Vibrio parahaemolyticus through targeting the blaCARB-17 like element, an intrinsic β-lactamase gene that may also be regarded as a novel species-specific genetic marker of this organism. Phylogenetic analysis showed that blaCARB-17 like genes were more conservative than the tlh, toxR and atpA genes, the genetic markers commonly used as detection targets in identification of V. parahaemolyticus. Our data showed that this blaCARB-17-specific PCR-based detection approach consistently achieved 100% specificity, whereas PCR targeting the tlh, toxR and atpA genes occasionally produced false positive results. Furthermore, a positive result of this test is consistently associated with an intrinsic ampicillin resistance phenotype of the test organism, presumably conferred by the products of blaCARB-17 like genes. We envision that combined analysis of the unique genetic and phenotypic characteristics conferred by blaCARB-17 shall further enhance the detection specificity of this novel yet easy-to-use detection approach to a level superior to the conventional methods used in V. parahaemolyticus detection and identification.